Propaganda Model Sinkretis Etis sebagai Budaya Tandingan terhadap Penistaan Agama di Media Sosial: Tinjauan Khusus Terhadap Kasus Joseph Paul Zhang - Jefri Andri Saputra (Jurnal Teologi Pambelum, 2023)
The case on religious blasphemy is still a part of religious conflict in Indonesia. Social media has a very crucial role in this case. Apart from going through the legal process, the settlement of this case is still oriented towards each religions. Therefore, the author recommends propaganda of syncretic-ethical awareness on social media as a counter-culture to religious blasphemy. The approach used in this paper is counterculture. The author concludes that social media is still dominated by content that is destructive to religion. Therefore, the ethical-syncretic awareness needs to be propagated as constructive content towards religion.